2019
DOI: 10.1097/txd.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Behavioral Versus an Educational Weight Management Intervention After Renal Transplantation: A Randomized Controlled Trial

Abstract: Supplement 1: Further description of the intervention At the beginning of each counselling session, the APN assessed the patient's general wellbeing to learn about individual difficulties and challenges. Then she asked about the patient's weight and degree of physical activity. Moving on, she explored patients' attitudes towards medically desired behaviors and assigned the corresponding stage of change as described in the transtheoretical model 1 :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…The individual study sample sizes ranged from eight [41] to 452 participants [42]. Two of the four studies include other transplant populations [43,44]; however, one author was able to provide data for the KTR sub-group on request [43].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The individual study sample sizes ranged from eight [41] to 452 participants [42]. Two of the four studies include other transplant populations [43,44]; however, one author was able to provide data for the KTR sub-group on request [43].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Six studies reported body weight only [39,41,44,47,48,50], four reported BMI [43,45,49,51], and six reported both body weight and BMI [36,42,43,46,52,53] post-intervention. Seven out of the sixteen studies recorded body weight or BMI at an interim time point of three to six months, and at a one-year follow-up [36,39,45,49,50,52,54].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations